Wage Determination in Russia: An Econometric Investigation - Mark E. Schaffer; Peter J. Luke (Institute for the Study of Labor (IZA), 2000)
Using a firm level dataset from four regions of Russia covering 1996/97, an investigation was carried out into how the surplus created within the firm is divided between profits and wages. An efficient bargaining framework based on the work of Svejnar (1986) is employed which takes into account the alternative wage or outside option available to employees in the firm as well as the value added per employee. Statistical differences in the share of the surplus taken by employees employed in state, private and mixed forms of firms are found. In addition, the results prove sensitive to the presence of outliers and influential observations. A variety of diagnostic methods are employed to identify these influential observations and robust methods are employed to lessen the influence of them. Whereas in practice some of the diagnostic and robust methods utilised proved incapable of identifying or accommodating the gross outlier(s) in the data, the more successful methods included robust regression, Winsorising, the Hadi and Siminoff algorithm, Cook?s Distance and Covratio.
Keywords: C21; J30; 330; Russian labour markets; efficient bargaining; outliers; regression diagnostics; robust regression; Lohn; Lohnverhandlungen; Eigentümerstruktur; Schätzung; Russland